Vegetative Growth of Sweet Corn (Zea mays L. Saccharata) Due to Difference Doses of Horse Manure Compost and NPK Fertilizer - Ahmad Raksun; Moh Liwa Ilhamdi; I Wayan Merta; I Gde Mertha (Jurnal Penelitian Pendidikan IPA, 2021)
Sweet corn has a sturdy and strong stem growth and is very suitable for cultivation in tropical climates. Research on the effect of horse manure compost combined with NPK fertilizer on the growth of sweet corn has been done with the aim of obtaining information: (1) the effect of different doses of horse manure compost on the growth of sweet corn, (2) the effect of different doses of NPK fertilizer on the growth of sweet corn, (3) The interaction effect of horse manure compost and NPK fertilizer on sweet corn vegetative growth. The application of NPK fertilizer was carried out with 4 treatment doses while the application of horse manure compost was carried out with 5 treatment doses. In this study, information was obtained (1) the application of NPK fertilizer increased the growth of sweet corn, (2) the application of horse manure compost increased the growth of sweet corn, (3) There was no increase in growth of sweet corn due to the combination treatment of NPK fertilizer and horse manure compost